African Unions Under Structural Adjustment Programs - Tidjani, Bassirou (Relations industrielles / Industrial Relations, 1998)
In most African countries, structural adjustment programs constituted the context of industrial relations conflicts during the 1980s because they had a negative effect on social and working conditions. A study discusses African labor's responses to its deteriorating conditions, and to states' attempts to limit labor's demands. It concludes that structural adjustment programs were implemented in all African countries despite labor's resistance. The degree of implementation depended on governments' repressive capabilities, workers' traditions of striving for independent organizations, and on unions' perceptions of the issue and their responsibilities under prolonged economic crises.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Impact analysis; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Structural adjustment; Studies